HIV/AIDS Knowledge and Attitude among High School Students in Shiraz, Iran in 2015 - Abbas Dehghani; Parvin Dehghani; Behzad Dehghani (Mashhad University of Medical Sciences, 2017)
Background & aim: Acquired immune deficiency syndrome (AIDS) is an infectious disease caused by human immunodeficiency virus (HIV). The awareness of HIV preventive measures and its transmission routes have an important role in controlling the HIV infection in the society. Regarding this, the present study aimed to investigate the awareness and attitudes of the high school students regarding HIV/AIDS infection in Shiraz, Iran, in 2015. Methods: This cross‐sectional study was conducted on 102 students, selected form six high schools. The students and schools were selected using the random sampling technique. The data were collected using a standard researcher-made questionnaire. The data analysis was performed using the Chi-square test through SPSS version 18. Results: As the results of the present study indicated, 55% of the participants were male, and the majority of them were about 17-18 years old. The participants' general knowledge about HIV was found to be at moderate level. However, they had insufficient awareness of the associated transmission routes and major causes of this disease. The students majoring in biological sciences were more aware of this issue than other students. In addition, the majority of the students had highly positive attitudes towards the AIDS patients and confirmed their right to live and use all facilities. However, a large proportion of the students denied to share a location or personal items with these patients. Conclusion: According to the findings of this study, almost all students had high level of general information about HIV. Nonetheless, given the students' low awareness and knowledge levels about the HIV transmission routes, the administration of the related educational programs is an urgent need to correct the students' misconceptions about the HIV patients and improve their knowledge in this regard.